Animal parade. Issue 2 (3rd April 2019) - Collins, Christopher C.
ABSTRACT: Animal Parade engages ethical questions about how we constitute relationships among human animals, nonhuman animals, and the environment. The script uses posthumanist theory, through aesthetic performance, to address how discursive structures produce, limit, or reinforce humanist assumptions that lead to environmental exploitation. In light of such concerns, the show challenges audiences to examine performative and nonlinguistic rituals of kin-making to address issues of the Anthropocene.